Різновиди типів відношення до хвороби при офтальмологічній патології - Саржевський, Сергій Никодимович; Саржевська, Людмила Едуардівна; Sarzhevskyi, S. N.; Sarzhevska, L. E. (My University, 2021)
Мета. Дослідити дезадаптаційні типи відношення до хвороби в офтальмологічній практиці. There were 74 patients who were treated in the Ophthalmic Department of Eye Microsurgery. The psychological test methodology “type of attitude towards the disease” was carried out. In 57 patients (73%), maladaptive behavior of an inter or intrapsychic orientation was revealed, which prevailed in the affective sphere and showed different types of response to the disease.
Varieties of types of attitude to the disease when ophthalmic pathology